On the Triviality of the Principle of Compositionality - Tolgahan Toy (Felsefe Arkivi)
The principle of compositionality states that the meaning of an expression is a function of the meanings of its parts. The principle is based on Gottlob Frege’s works that consider linguistic meaning in the function-argument structure. Through Richard Montague, this principle has taken a central place in formal semantics. According to the principle, a homomorphic relationship exists between linguistic and semantic structures. Proponents of the principle argue that compositionality makes an important contribution to the systematic and productive structure of language. Contrary to this view, Wlodek Zadrozny has argued compositionality to not contribute to the systematic structure of language. To justify this claim, Zadrozny put forward proof showing that any semantic structure can be encoded compositionally. Zadrozny also attributed the existence of such a semantic function for any semantic structure to Peter Aczel’s non-well-founded set theory. The solution lemma informs one that such a meaning function exists. However, an important objection to Zadrozny’s claim is found. The obtained semantic structure has been claimed to be insufficient for encoding the original semantic structure. The basis of this claim involves the phenomenon of synonymity. Non-compositional semantic structures in which synonyms do not follow the principle of substitution have been argued as being unable to be represented by compositional semantics. This work examines Zadrozny’s proof and answers the objection by claiming synonymity, being the subject of this objection, is not a property that needs to be preserved.